Fertilización con diferentes abonos orgánicos en colines de banano en vivero - Alejandro Reyes, Joaquín Edison (2009)
In the parish San Rafael of the canton Tenguel of the province of the Guayas one worked with the asexual propagation of banana tree of the clone Cavendish gigantea to leave of taken colines of plants elites selected in the field to use in the establishment of plantations of organic banana tree following the limits of the certificadora OKO BCS. The outlined objectives were: 1. to determine the best treatment with organic payments in banana tree colines in nursery. 2. to evaluate the effect of acceleration in growth of banana tree colines. The analyzed variables were, height of the colín to the 30, 45 and 60 days after the siembra, number of roots to the 60 days, grosor of the pseudotallo, number of leaves to the 60 days and biomass of the plant. The treatments were assigned to the experimental units following the limits of the design blocks at random with five treatments and six repetitions. The experimental unit was integrated by 20 polyethylene cases containing a sustrato and the colines to those that are incorporated the doses of the treatments. The obtained results evidenced that the incorporation of organic materials in the colines enraizamiento for new plantations cooperates to the growth and development to foliate and of the plants. The height of the plants and especially the rate of daily growth was superior that the one observed in the witness; reached to 1,23 cm per day in the colines paid with bokashi 160 g/colín, compared with the witness that grew to a rhythm of 0,50 cm/día, consequence of that which to the 60 days, the plants presented bigger height. For the number of leaves for plant, statistical significancia was also obtained, standing out the treatment bokashi 160 g/p. In the variable number of roots, it was not obtained significant differences that which is attributed to that the emission of roots, is bound to genetic factors. In grosor of the shaft in the short period of time of 60 days, significant answer was not obtained to the application of the organic payments. In the biomass for plant statistical significancia was obtained for treatments occupying the first place the treatment bokashi 160 g/hill with an average of 478 g/p, without ending up differing statistically of the witness but if with relationship to the plants fertilized with phosphoric rock, in those that it was obtained the smallest weight or biomass.